Estudio de las característica de la cascara de coco (Cocos nucifera) para la obtención y producción de tableros aglomerados y carbón activado - Garofalo Zambrano, Stefanno Adrian; Hernandez Mejia, Jessica Diana (2018)
This research work aims to give a use to coconut waste in the construction industry and health, to greatly reduce pollution, coconut shell, coarse straw and bast could be used as raw material, for multiple industrial purposes. In the industry of agglomerate boards, conventional raw material is used. The felling of trees is their main source of supply, using many special timber products, as a consequence this directly affects the environment and the ecosystem due to the indiscriminate felling of trees, diminishing forests and places. The activated carbon industry has been growing in recent times being its use increasingly common and more reliable having as a base of production of raw material of vegetable origin being this transformed from products such as palm. The research model used in the exploration is experimental, constituting a general overview that brings the investigation closer to an exploratory reality for field research. Factorial design agglomerated board of coconut nucifera (A x B x C), with levels A = 2 (a_0, a_1); B = 3 (b_0, b_1, b_2) YC = 2 (c_0, c_1), obtaining 12 treatments that will be submitted to a study in which 2 repetitions will be applied, obtaining a total of 24 treatments to be evaluated in Analysis of variance (ANOVA) and Tukey test in the Statgraphics and info Stat program. For activated carbon a factorial design A x B between its levels is A (3); B (2) resulting in 6 treatments, which will be subjected to an experimental study, proposing 2 repetitions for the research, obtaining 12 samples. For the evaluation of the effects between the levels and treatments, the tukey test will be carried out in the Statgraphics and InfoStat program. According to the statistical studies carried out for agglomerated boards, it was advisable to work with dry coconut for the states of coconut and urea formaldehyde resin in terms of binder, since they are the most optimal, considering the activated carbon, the best results were evident in the dry coke dare the physical method of activation. Keywords Coconut nucifera, organic residue flexion, torsion, screw pull, binders, agglomerates, chemical activation, physical activation,